2020
DOI: 10.3389/fnana.2020.00027
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Reciprocal Structural Network Interactions Between Bilateral Crus Lobes and Broca’s Complex

Abstract: While the proximal dentatothalamocortical tracts are considered pivotal in the occurrence of cerebellar mutism syndrome (CMS) after medulloblastoma resection, how the cerebellum participates in motor-speech networks through direct structural connectivity is still unclear. Via tractography, we provide evidence of cerebellar streamlines projecting into the left inferior frontal gyrus majorly connecting Broca's complex and the bilateral Crus lobes. The streamlines, named Crus-Broca tracts, originated from the bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 97 publications
0
5
0
Order By: Relevance
“…Such evidence may be the basis of information interplay between the cerebrum and the cerebellum in language processing. In the theory of cerebellar internal models, the cerebellum plays a role in motor speech planning by transmitting predictions on coming linguistic information and modifying speech execution if needed [ 44 ]. Through the dense structural connectivity between the cerebrum and the cerebellum, the linguistic cerebellum receives information from the frontotemporal area during speech production [ 45 ] and conveys predictive information to the prefrontal cortex to ensure accurate actual expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such evidence may be the basis of information interplay between the cerebrum and the cerebellum in language processing. In the theory of cerebellar internal models, the cerebellum plays a role in motor speech planning by transmitting predictions on coming linguistic information and modifying speech execution if needed [ 44 ]. Through the dense structural connectivity between the cerebrum and the cerebellum, the linguistic cerebellum receives information from the frontotemporal area during speech production [ 45 ] and conveys predictive information to the prefrontal cortex to ensure accurate actual expression [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020, a tractography study published in Frontiers in Neuroanatomy found that the Crus-Broca tracts, which originated from the bilateral Crus lobe, synapsed in the dentate nucleus, ascended into the superior cerebellar peduncle, passed through the left red nucleus and the left thalamus, and terminated at the subregions of Broca's complex. Conversely, the Broca-Crus tracts originated from the subregions of Broca's complex, and the majority of efferent nerve bers terminated at the right Crus lobes [59]. However, this nding needs further veri cation.…”
Section: Mechanisms Of Ppcms 4311 Anatomical Substratesmentioning
confidence: 94%
“…6. 59 A pre-operative scoring system for predicting risk of postoperative pediatric cerebellar mutism syndrome [43]. 6.48…”
Section: 65mentioning
confidence: 99%
“…We obtained access to restricted data in the HCP. The preprocessing of HARDI data was performed using HCP pipelines (version 3.26.0) ( Glasser et al, 2013 ) and is described in detail in our previous work ( Zhang et al, 2020 ). T1-weighted images were linearly registered to diffusion space using the “flirt” tool in FSL 6.0.1 with 12 degrees of freedom ( Jenkinson et al, 2002 ).…”
Section: Methodsmentioning
confidence: 99%
“…The fiber orientation distribution was generated, which was described in detail in our previous work ( Zhang et al, 2020 ). Then, whole-brain tractography was performed with Mrtrix3 in the native space using the following parameters: -act, -crop_at_gmwmi, -maxlength 200, -select 5M, -cutoff 0.1 -seed_gmwmi, -angle 30, and -iFOD2 ( Tournier et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%